Perception, satisfaction, and self-regulation in a blended learning environment during COVID-19 pandemic among health sciences students: A cross-sectional survey - Naina Thapa; Daisy J Lobo; Radhika R Pai (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: The coronavirus disease (COVID-19) pandemic has severely impacted the health status of the people and the education of the students affecting their learning process and performance in examinations. Blended learning (hybrid learning) has evolved as one of the convenient and innovative methods of using technologies with the integration of traditional methods, significantly when face-to-face interaction is compromised. This study aimed to assess perception, satisfaction, and self-regulatory learning behaviors among undergraduate health sciences students.METHODS AND MATERIAL: A descriptive cross-sectional survey was carried out among 550 undergraduate students. The tools used for data collection were demographic proforma, perception scale, satisfaction questionnaire, and self-regulation learning scale, which were self-report questionnaires. The data were analyzed using Spearman's rank correlation and Chi-square test.RESULTS: About 378 (68.7%) out of 550 students preferred traditional face-to-face learning before the COVID-19 pandemic, whereas 276 (50.2%) students chose blended learning after the pandemic. About 424 (77.1%) perceived blended learning positively, 267 (48.5%) were moderately satisfied, and 377 (68.5%) of the students had moderate self-regulation in blended learning. The study revealed a strong, positive relationship, between perception (r = 0.817, P < 0.001), satisfaction (r = 0.710, P < 0.001), and self-regulation (r = 0.722, P < 0.001) in the blended mode of learning. Age, course, year of study, and preference of learning mode were significantly associated with perception, satisfaction, and self-regulation in blended learning at P < 0.05. However, perception, satisfaction, and self-regulation among students did not differ according to gender and students' previous exposure to a blended mode of learning at P > 0.05.CONCLUSIONS: To implement innovative pedagogical techniques using improvised technological assistance in teaching and learning, building up an effective blended learning environment within every institution is essential.